Factors affecting the Chinese cross border e-commerce export trade in the home based economy: Exchange rate as a moderator - Zhu, Lili (2024)
Over the last two decades, with the practice of the "One Belt and One Road" initiative, China's cross-border e-commerce import and export trade has been in the right track of its rapid development. In sharp contrast to the downturn of traditional foreign trade, the rapid development of cross-border e-commerce trade has gradually broken the traditional mode of China's foreign trade and become a new force for China's trade development. In this vein, the objectives of the study were: (i) To examine the factors significantly affecting China's cross-border e-commerce export trade; (ii) To identify the moderating effect of exchange rate between GDP per capita and China’s cross- border e-commerce export; (iii) To determine the moderating role of exchange rates on the effects of consumption gap on China's cross border e-commerce exports; (iv) To determine the moderating role of exchange rates on the effects of number of internet security servers on China's cross border e-commerce exports; (v) To determine the moderating role of exchange rates on the effects of FDI on China's cross border e- commerce exports; (vi) To determine the moderating role of exchange rates on the effects of educational level on China's cross border e-commerce exports; (vii) To determine the moderating role of exchange rates on the effects of distance on China's cross border e-commerce exports; (viii) To determine the moderating role of exchange rates on the effects of population on China's cross border e-commerce exports. This thesis first summarized the key concepts of China's cross-border e-commerce trade. The research model used in this thesis was the improved trade gravity model, and then provided the Two-way fixed-effects model to analyze the influential factors of Chinese cross border e-commerce export trade. It involved factors such as consumption gap, exchange rate against US dollar, educational level, population and Internet usage based on the data of the 10 sample destinations with the highest cross-border e-commerce export volume in 2022. An empirical analysis of the cross- border e-commerce trade with the said destinations was conducted from 2013 to 2022. The findings were: GDP per capita, the Difference in GDP per capita, Internet scale, education level and FDI were s positively significant related to China’s cross-border e-commerce export. However, the independent variables of Distance and Population were not significantly related to China’s export cross-border e-commerce. This thesis used the exchange rate as the moderating variable to analyze the relationship of the above five significant variables and the China’s cross border e-commerce export. The result of the moderating effects showed all significantly related to China’s cross border e-commerce export except the variable of the Difference in GDP per capita which is not significant. Finally, this thesis provided the discussion, recommendations, limitations and the conclusion. In all, the results of empirical analyses are paramount important to the government of China and related enterprises to apply the right strategies to improve competition in international cross-border e-commerce trade.